Job Satisfaction Karyawan Perbankan Memediasi Transformational Leadership dan Job Performance - Anggoro Anom; Wiwik Robiatul Adawiyah; Dita Oki Berliyanti (Universitas Batanghari, 2023)
This study uses 3 variables consisting of: 1 independent variable, namely transformational leadership, 1 mediating variable, namely job satisfaction and 1 dependency variable, namely work performance, which aims to analyze the effect of transformational leadership on work performance which is mediated by job satisfaction in employees of PT. Bank Mandiri Tbk. Jakarta's Big Rice Field. The sample used in this study were employees of PT. Bank Mandiri Tbk. Paddy Field, Central Jakarta. Sampling used the cluster random sampling method, through a survey using a questionnaire with a total of 190 respondents and the data analysis method in this study used the Structural Equation Model (SEM) with AMOS version 23 software. through a survey using a questionnaire with the results of this study indicating that transformational leadership positive effect on job satisfaction. However, it does not have a significant effect on work performance. If you look at the role of Job Satisfaction as a Mediation variable, it is enough to influence transformational leadership on Job Performance at PT. Bank Mandiri Tbk. Jakarta's Big Rice Field. Thus, the conclusions obtained indicate that employees with high job satisfaction tend to be good at their jobs compared to employees with low job satisfaction. In addition, the work performance of employees with high transformational leadership is greater than that of employees with low transformational leadership. In addition to the direct effect, this study shows that job satisfaction has a significant mediating role in the relationship between transformational leadership and performance. These findings reveal important theoretical clues that transformational leadership as a personal ability can influence work performance not only directly but also indirectly through its positive influence on job satisfaction.